Immunohistochemical Features of MMP-9 and pSTAT1 in Granuloma Annulare and Sarcoidosis: A Comparative Study of 62 Cases - Ze Wu; Linghui Li; Hui Qu; Rui-Qun Qi; Jun Niu (Journal of Immunology Research, 2023)
Background. Granuloma annulare (GA) and sarcoidosis are granulomatous inflammatory diseases that share similarities. Objective. To identify the histological and immunohistochemical (IHC) features of GA and sarcoidosis. Methods. A retrospective review of 36 patients with GA and 26 with sarcoidosis was performed. Results from hematoxylin and eosin (H&E) staining and IHC staining of MMP-9 and pSTAT1 within the skin lesions of GA and sarcoidosis were analyzed, and random forest was applied for developing a predictive model. Results. Significantly greater expressions of MMP-9 (especially in elastic fibers, EFs, P<0.0001) and pSTAT1 (P=0.0003) were observed in lesion samples of GA versus sarcoidosis patients. In GA patients, MMP-9 was significantly upregulated in the interstitial type (P=0.0222), while staining of pSTAT1 was positively correlated with the area of mucinous collagen in palisading GA (R=0.5356, P=0.0484). In sarcoidosis patients, MMP-9 (R=−0.7127, P=0.0009) and pSTAT1 (R=−0.5604, P=0.0067) were found to show stronger expressions in lesions with less lymphocyte infiltration. The predictive model demonstrated an AUC of 0.9675. Conclusion. These results indicate that MMP-9 and pSTAT1 might exert roles in granulomatous inflammation in different modes, and the presence of more robust MMP-9 staining in EFs appears to be more suggestive of GA.